Coordination of Time-Varying Price Supply Chain with Risk-Averse Members under Random Order Response Time - Shuanjun Song (Mathematical Problems in Engineering, 2020)
A joint contract is proposed to coordinate the time-varying supply chain of risk-averse manufacturers and retailers. The joint contract uses price reduction subsidies and revenue-sharing strategies to enable manufacturers and retailers to share risks and achieve overall coordination of the supply chain. Firstly, a centralized and a decentralized decision-making model of the risk-averse supply chain are established. On this basis, reasons for the supply chain failure to coordinate are analyzed, and a joint contract is designed. Then, the specific form of the joint contract is given. Finally, the coordination effect of the joint contract is quantitatively analyzed through numerical analysis.